Recent Developments in the Methods of Estimating Shooting Distance - Arie Zeichner; Baruch Glattstein (The Scientific World Journal)
A review of developments during the past 10 years in the methods of estimating shooting distance is provided. This review discusses the examination of clothing targets, cadavers, and exhibits that cannot be processed in the laboratory. The methods include visual/microscopic examinations, color tests, and instrumental analysis of the gunshot residue deposits around the bullet entrance holes. The review does not cover shooting distance estimation from shotguns that fired pellet loads.